2000
DOI: 10.1080/09663690024843
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work, Childcare and Domestic Work: Divisions of labour in Canadian paper mill communities

Abstract: The growing prevalence of shift work and non-standard working hours is challenging many taken-for-granted notions about family and household life. This paper examines how rotating shift-schedules shape household strategies with regard to childcare and unpaid domestic work. In 1993-1994 we conducted in-depth interviews with 90 predominantly male newsprint mill-workers and their spouses living in three communities located in different regions of Canada. Our analysis is based on these interviews as well as data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
0
16
0
3
Order By: Relevance
“…For example, Preston et al (2000) undertook a comparative study of shift work in three paper mill communities, and found that the responsibility to adapt childcare and other household responsibilities to men's shift work rotations fell almost entirely upon their wives, whether or not their wives were working outside the home. The authors also found that employed women were likely to quit their jobs in order take care of their children, or, in one community, to hire live-in nannies.…”
Section: Materials Contradictionsmentioning
confidence: 98%
“…For example, Preston et al (2000) undertook a comparative study of shift work in three paper mill communities, and found that the responsibility to adapt childcare and other household responsibilities to men's shift work rotations fell almost entirely upon their wives, whether or not their wives were working outside the home. The authors also found that employed women were likely to quit their jobs in order take care of their children, or, in one community, to hire live-in nannies.…”
Section: Materials Contradictionsmentioning
confidence: 98%
“…Urban form and process and locational differences within cities thus actively construct gender as well as other social relations: 'cities are not just the scenery for the playing out of gender' (Garber & Turner, 1995, p. xviii). For example, feminist urban geography has repeatedly shown how differences in local contexts of employment and neighbourhood are crucial to understanding the ways that gender identities, performances and relations are negotiated and reshaped in the domestic sphere (Dowling, 1998b;Holloway, 1998;Rose, 1999a;Bondi & Christie, 2000;Preston et al, 2000;Duncan & Smith, 2002).…”
Section: Gendering the Urban And Spatialising Gendermentioning
confidence: 99%
“…Pesquisas têm revelado como este papel assumido pela mulher tem repercutido na dinâmica familiar, nas questões conjugais, bem como na educação dos filhos (Bertolini, 2001;Garcia, 2001;Preston, Rose, Norcliffe e Holmes, 2000;Arrighi & Maume, 2000). Nesse sentido, talvez um dos aspectos mais desafiantes a ser mencionado envolva a necessidade de essas mulheres conciliarem as funções familiares com as acadêmicas e profissionais.…”
Section: Introductionunclassified
“…Nesse sentido, talvez um dos aspectos mais desafiantes a ser mencionado envolva a necessidade de essas mulheres conciliarem as funções familiares com as acadêmicas e profissionais. Estes estudos apontam as transformações nos papéis e funções delegados para homens e para mulheres que possuem uma carreira, dedicam-se a uma profissão e precisam seguir criando e educando os filhos (Souza, 2001;Andrade, Postma e Abraham, 1999;Preston, Rose, Norcliffe e Holmes, 2000). No entanto, pouco tem sido relatado a respeito das peculiaridades estruturais das famílias em que a mulher representa a principal fonte de renda.…”
Section: Introductionunclassified